Long-Term No-Till Conservation Agriculture and Nitrogen Fertilization on Soil Micronutrients in a Semi-Arid Region of South Africa - Samukelisiwe G. Zulu; Lembe S. Magwaza; Nozipho M. Motsa; Nkanyiso J. Sithole; Khayelihle Ncama (Agronomy, 2022)
Knowledge of the long-term complex relationship between soils, crops, and management practices, such as conservation agriculture, is critical in developing nutrient management strategies to optimise crop yields. This study examined the concentration, and the distribution of, soil micronutrients along the soil profile (0–10, 10–20, and 20–30 cm depths) under different tillage practices: no-till (NT), rotational tillage (RT), and conventional tillage (CT), and nitrogen fertilizer application rates (0, 100, 200 kg/ha) in a semi-arid environment after 17 years of implementation of the trial. The results found the lowest concentration (p < 0.05) of copper (Cu) (1.254 mg/kg) and iron (Fe) (22.671 mg/kg) in CT compared to NT [Cu (1.447 mg/kg), Fe (41,156 mg/kg)] and RT [Cu (2.389 mg/kg), Fe (120,437 mg/kg)] treatments. This correlated with the lower soil pH in NT compared to CT treatment, and slightly higher (p > 0.05) under NT (1.782 mg/g) compared to RT (1.715 mg/g) and CT (1.750 mg/g). There were no differences (p > 0.05) in zinc (Zn) in NT (2.856 mg/kg) and RT (2.782 mg/kg) but CT (2.010 mg/kg) treatment was significantly (p < 0.05) lower compared to these treatments. Manganese (Mn) also followed a similar trend whereby CT still had the lowest concentration (p < 0.05) of Mn (8.01 mg/kg) compared to RT (10.71 mg/kg) and NT (11.98 mg/kg). The concentration of Mn, Zn, and Fe was found to be similar (p > 0.05) with an increase in sampling depths. On the other hand, Cu was found to be different (p < 0.05) at different sampling depths. Manganese (10.46 mg/kg) and Soil Organic Carbon (SOC) (2.026 mg/g) were found to be concentrated near the 0–10 cm soil surface depth while Zn (2.558 mg/kg), Fe (66,217 mg/kg) and Cu (1.867 mg/kg) were more at the 20–30 cm depth in reduced tillage treatments. The results also showed no differences (p > 0.05) in the concentration of Cu, Mn, and Zn at different levels of nitrogen fertilizer under all tillage treatments. It was concluded that NT and rational tillage with mulch, favoured the availability of micronutrients (Cu, Mn, Fe, and Zn) in the studied cropping system.